Межі Волинської землі кінця Х — середини XIV ст. у світлі археологічних, писемних та топонімічних джерел - Кучинко, М. (Археологія, 2002)
У статті на основі археологічних, писемних i топонімічних даних розглянуто проблему етноплемінних і адміністративних меж Волинської землі кінця X — середини XIV ст. В статье на базе археологических, топонимических и письменных источников по-новому освещается проблема рубежей Волынской земли. Определены племенные рубежи на севере с ятвягами, на западе с поляками, на юге с хорватами, на востоке с древлянами и на северовостоке — с дреговичами. Одновременно определены государственная граница с Польшей на западе и административная — с Галицкой землей на юге, Киевской — на востоке и Турово-Пинской — на северо-востоке. Based on the archaeological, toponymical, and written sources, the article, in a new way, elucidates the problem of the borders of the Volyn land. The author defined the tribal borders as the Jatvyags in the north, the Poles in the west, the Croats in the south, the Drevlyans in the east, and the Dregoviches in the northeast. At the same time, the state border with Poland in the west and the administrative borders with the Galich land in the south, the Kyiv land in the east, and the Turovo-Pinsk land in the northeast are cleared out.